The extent of knowledge abd compliance with the copyright law of the librarians of the Department of Justice and its attached agencies - Santos , Marilou M. (School of Library and Information Studies, University of the Philippines Diliman, 2008)
Law librarians deal mainly with legal information and materials and it is important that they are aware of the law affecting libraries and librarians, like the copyright law. This study exemplifies the librarians of the Department of Justice (DOJ) and its attached agencies having operational libraries, on the extent of their knowledge and compliance with the copyright law, focusing on their reprographic reproduction practices. The study aims to determine the librarians' extent of knowledge and compliance with the copyright law, and to describe the reproduction practices and specific institutional cases concerning copyright-related policies.